145k views
3 votes
If f(2x)= 3x-1, find f(​

1 Answer

4 votes

Answer:

Explanation:

I'm assuming that you're looking for f(x) here given that f(2x) = 3x - 1.

The key is to make a substitution for f(2x) so things are easier for us in the long run. Let u = 2x. Now solve that for x so x is in terms of u:

x = u/2. Therefore, f(2x) becomes f(u) and


f(u)=3((u)/(2))-1\\f(u)=(3u)/(2)-1\\f(u)=(3u)/(2)-(2)/(2)\\f(u)=(3u-2)/(2)and now we can replace the u with the x (to put it back in terms of x):


f(x) =(3x-2)/(2) We can check our work by using that and evaluating it at f(2x). If we are right, then f(2x) = 3x - 1.

f(2x) =
(3(2x)-2)/(2) and


f(2x)=(6x-2)/(2)\\f(2x)=(2(3x-1))/(2)\\f(2x)=3x-1

User Keshaun
by
4.2k points